Proximal humerus fractures operated with PHILOS plate: 4 year prospective study - Kulkarni, Shreepad; Kulkarni, Avinash; Patel, Amit; Gupta, Tapan (International Journal of Research in Orthopaedics, 2017)
Background: Fractures of proximal humerus are still an unsolved problem in many ways. Locked plating is becoming more common; precise knowledge of and experience with the surgical technique is required to maximize clinical outcomes. However the goal of proximal humerus fracture fixation should be stable reduction allowing early mobilization. This study is conducted to study the results and complications of proximal humeral fractures treated by anatomic locking compression plate (PHILOS- proximal humerus interlocking system) and PHLP- Pro. Methods: This is a 4 year prospective study, conducted in the department of Orthopaedics in Shri B M Patil Medical College & Hospital, Vijaypur. Displaced two part, three part and four part fractures of proximal humerus with or without shoulder dislocation including fractures involving osteopenic bone were included. The functional assessment was done according to constant Murley score and DASH score at the end of 6 months. Results: Out of 60 patients, 56 were available for follow-up: 24 patients having excellent results (4 are 2 part, 20 are 3 part fractures), 32 patients having good results (22 are 3 part, 10 are 4 part fractures). None of the patients had fair or poor results. Conclusions: In conclusion, the internal fixation of proximal humeral fractures with the use of anatomic locking compression plates yields reliable results when utilized correctly. We believe that, provided the correct surgical technique is used by competent surgeon, the anatomic locking compression plate is suitable for the stabilization of proximal humeral fractures and can lead to a good functional outcome.